The PCL-R, PAI, and Rorschach as Predictors of Institutional Misconduct with Incarcerated Women - Smith, Jason M. 19XX- (Women & criminal justice, 2022)
Managing the incarcerated population is the primary task within correctional settings. Using psychological assessment to predict institutional behavior, the psychologist has a unique set of skills essential to the management of prisoners. PCL-R, PAI, and Rorschach data were compared with institutional infractions (total, physical, verbal, non-aggressive) among 126 incarcerated women. Multiple binary logistic regression analyses were used which found significant correlations between PCL-R total score, PAI scales (BOR, ANT, VPI), and Rorschach variables (ROD, EGOI, TCI, AgPot, AgPast, SumV, SumC’, MOR) with total, verbal, physical, and nonviolent incident reports. Each of these measures adds incrementally to the assessment and understanding of institutional misbehavior for incarcerated women. Clinical implications of the findings were presented.